COVID-19 Pandemic and Mental Health of Doctors: An Observational Analytical Study from a Dedicated COVID Hospital. - Khatoon, F; Singh, A; Jilani, AQ; Ahmad, A; Haq, M; Pandey, S (International Journal of Human and Health Sciences (IJHHS), 2021)
Objective:Doctors experienced unprecedented levels of workload and pressure since the outbreak of COVID-19, making them more vulnerable to adverse psychological outcomes. While frontline healthcare workers face a substantially higher risk of susceptibility to infection due to excessive COVID-19 exposure, little is known about its impact on doctors not directly posted with COVID-19 patients. Our study was focused on studying the impact of COVID-19 pandemic on mental health of this subgroup of doctors. Materials and Methods: From April 1st to July 31st, 2020, a cross sectional web-based survey was conducted at a COVID-19 dedicated tertiary care hospital. The study was conducted using standard questionnaires measuring adverse psychological outcomes including DASS-21 and WHO-5. Univariate and multivariate logistic regression were used to examine the determinants of adverse psychological outcomes. Results and Discussion: 145 doctors completed the survey questionnaire with over 71% females and 29% males. The overall prevalence of anxiety, depression and stress among doctors was 38.6%, 41.37% and 32.42% respectively. The overall well-being score was found to be 52.77 + 24.19 with a median [IQR] of 52. Conclusion: A high incidence of adverse psychological outcomes are observed amongst doctors during COVID-19 pandemic, even when they are not directly involved in the care of COVID-19 patients. Stress, anxiety and depression have an inverse relationship with age and marital status. Anxiety has an inverse relationship with religious beliefs. International Journal of Human and Health Sciences Vol. 05 No. 03 July’21 Page: 297-306